“What Other Information Is There?”: Identifying Information Gaps, Perceptions and Misconceptions on COVID-19 Among Minority Ethnic Groups in the Netherlands - Bakuri, Amisah Zenabu; Antwi-Berko, Daniel (Frontiers in Health Services, 2022)
Background Multiple media platforms and various resources are available for information on the novel coronavirus disease (COVID-19). Identifying people's preferences is key to building public confidence and planning for successful national or regional health intervention strategies. Methods Using exploratory mixed-methods including a short survey, interviews and participant observation, this cross-sectional study of 160 respondents from the Ghanaian-Dutch, Afro and Hindustani Surinamese-Dutch communities in Amsterdam, the Netherlands was conducted. Data collected between February to April 2021, included demographics characteristics, knowledge, opinions, preferred source of information, behavioral factors, and information gaps on COVID-19 prevention measures, responses and decision-making of respondents. Descriptive statistics and follow-up in-depth interviews were conducted to determine the relationship between respondents' demographics, information sources, and attitudes/behaviors toward COVID-19. Results The findings of this study indicated that although many of the respondents from these communities had good knowledge on COVID-19, its modes of transmission and prevention measures, their willingness to take up initiatives and prioritize self responsibility toward their health are tied to their communal life. The respondents in this study demonstrated high value for social lives and relied on their connections with friends and families in shaping, obtaining, processing and utilizing COVID-19 information to build a sense of responsibility toward the uptake of COVID-19 prevention measures despite recent decline in number of cases. Conclusion This sense of responsibility means their active participation and ownership of interventions to address the specific personal concerns and that of their community. However, different factors play influential roles toward the behavior choices of our respondents regarding the COVID-19 prevention.